Solos Amazônicos: Atributos Físicos, Químicos, Erodibilidade E Suscetibilidade Magnética 2022
DOI: 10.22533/at.ed.4732219054
|View full text |Cite
|
Sign up to set email alerts
|

Atributos Físicos Do Solo Em Áreas Sob Conversão Floresta/Pastagem No Norte De Rondônia, Brasil

Abstract: Direitos para esta edição cedidos à Atena Editora pelos autores. Open access publication by Atena Editora Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição-Não-Comercial-NãoDerivativos 4.0 Internacional (CC BY-NC-ND 4.0). O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores, inclusive não representam necessariamente a posição oficial da Atena Editora. Permitido o download da obra e o compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results observed for the F1 semivariograms highlight the correlated attributes and are more sensitive for defining management zones. Lima et al (2022) observed that environments that are more influenced by high sand and clay contents interfere with soil aggregation, compaction, porosity, and organic carbon accumulation. It is necessary to generate specific management zones that affect these soil properties.…”
mentioning
confidence: 99%
“…These results observed for the F1 semivariograms highlight the correlated attributes and are more sensitive for defining management zones. Lima et al (2022) observed that environments that are more influenced by high sand and clay contents interfere with soil aggregation, compaction, porosity, and organic carbon accumulation. It is necessary to generate specific management zones that affect these soil properties.…”
mentioning
confidence: 99%